"Competitive" Costs and the Rent of Business Ability - Wolfe, A. B. (Quarterly Journal of Economics, 1924)
Current tendencies in the study of cost theory, 41.—The indeterminate meaning of "market" and "competition" in economic literature, 47.—Discontinuity of retail markets; the fallacy in comparing the costs of firms serving different markets, 51.—"Marginal" buyers not effective in stimulating significant inter-market competition, 53.—The question of competition between wholesalers of clothing and of store equipment, 57.—"Competitive" costs in the great staple industries, 58. — Low costs and high profits not necessarily due to superior entrepreneural ability; devices for avoiding competition; advantages of priority; temporary and permanent advantages, 61.—Does competition compete? Why does not competition result either in uniform costs or in monopoly? 65.—Need of caution in inductive study, 66.—Need of study of the life histories of individual firms, 67.—Rent of superior entrepreneural ability inconsistent with the assumption of free price competition, 69.